Incidence of post-operative (caesarean section) infectious morbidities in cleansing and non-cleansing group after povidone iodine vaginal cleaning - Verma, Pragya; Chawla, Dolly; Khatri, Rashmi; Verma, Preeti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Despite of wide spread use of prophylactic antibiotics and various antiseptic measures, post-operative infection remains one of the significant and serious complication of caesarean delivery contributing to high maternal morbidity and mortality. Objective was to study the incidence of post-operative infectious morbidities in patients with/without povidone iodine vaginal cleansing done prior to caesarean section. Methods: A prospective randomized control study was done in the department of obstetrics and gynecology of Dr. Baba Saheb Ambedkar Medical College and Hospital, New Delhi. Results: Mean age of participants in group A is 26.22±2.47 years and in group B is 26.48±2.3 years. Majority women (84.0%) underwent emergency lower segment caesarean section (LSCS). (6.4%) women developed post-operative endometritis, out of which maximum (4.6%) belong to no vaginal cleansing group (B) compared to 1.8% in povidone iodine vaginal cleansing group(A), which is statistically significant (p=0.01). Over all (13%) women had post-operative fever, with significant difference among the two groups i.e. (8.6%) were in group B versus (4.4%) in group A (p=0.005). Conclusions: Povidone iodine vaginal cleansing prior to caesarean section is significantly effective in reducing post-operative infectious morbidities.